Оптимизация конструкции фрезерного комбайна на базе лунохода с помощью технологии имитационного динамического моделирования - Липин, Н К; Плетнёв, М А (Интеллектуальные системы в производстве, 2017)
The work presents the comparative analysis of the options of a design of the milling combine created on the basis of a moon rover by means of imitating calculations. The work is focused on the section "The federal space program of Russia for 2016-2025 - "Basic space researches" according to which the problem of creation of the milling combine for carrying out geological researches on a surface of other planets is actual. The research objective is optimization of a design of the milling combine created on the basis of a moon rover by means of technology of ultrahigh and polygonal dynamic 3D modeling. For achievement of a goal the technological chain which is conditionally divided into some main stages was used. Due to the insistence to resources and specifics of tasks imitating modeling was carried out by means of hardware-software complexes. Results in the form of models of the milling combine and a lunar surface are received. The interactive simulator functioning in modern full-scale technologies of virtual reality for training of future operators when performing missions to the Moon is created. The design shape conforming to requirements received by an iterative method of design can be applied in systems of information support at all stages of life cycle of a product. Carrying out such works is a necessary condition of providing prospects of use of systems of modeling, both for carrying out examinations, and in interests of the solution of perspective tasks of designing of space equipment.